PENAMBAHAN NAA DAN BAP TERHADAP MULTIPLIKASI SUBKULTUR TUNAS GAHARU (Aquilaria malaccensis Lamk) - anti, Juli; Wulandari, Reine Suci; Darwati, Herlina (JURNAL HUTAN LESTARI, 2013)
The benefits of Aquilaria malaccensis cause many people do the illegal activities to collect Aquilaria. Illegal logging causes Aquilaria in the endangered category species so that the export trade of this plant is limited. The problem of propagation of aquilaria can be solve with tissue culture techniques. The research objective is to determine the influencce of Naphthalene acetic acid (NAA) and Benzyl amino purine (BAP) on the development of subcultures best aloes. The research was conducted at the Laboratory of Silviculture Faculty of Forestry University Tanjungpura, observations made during six weeks. The method used in this study is factorial completely randomized design (CRD) in this study is factorial completely randomized design (CRD) with, Data were analyzed with analysis of variance and followed HSD test. such as ; NAA and BAP as factors with three concentration level and six replicant, as follows NAA (A) : 0.1 mg/l ; 0.15 mg/l ; 0.2 mg/l and BAP (B) : 2.5 mg/l ; 3.0 mg/l ; 3.5 mg/l). The results showed that the interaction between NAA and BAP concentrations has significantly influence to the development of Aquilaria subculture. In this study the best concentration is A1B1 (0.1 mg/l NAA and 2,5 mg/l BAP) where the number of shoots produced as many as 12 buds. Key words : Naphthalene acetic acid, Benzyl amino purine, Growth hormone, Subcultures and Aquilaria malaccensis.